Research in organizational change and development. Vol. 19 - Shani, Abraham B.; Woodman, Richard W.; Pasmore, William A. (Research in organizational change and development,, 2011)
Volume 19 of Research in Organizational Change and Development includes papers by an international and diverse set of authors including Michael Beer, Victor Friedman, Luiz Gomez & Donna Ballard, Ethan Berstein & Frank Barrett, Karen Jansen & David Hoffman, Guido Maes & Geert Van Hootegem, and Tobias Fredberg, Flemming Norrgren & Rami Shani and the ideas expressed by these authors are as diverse as their backgrounds. New methodologies are introduced, such as the strategic fitness process for engaging leaders in better understanding the reactions of employees to strategic change efforts (Beer); Jazz as a metaphor for organizational improvisation (Bernstein & Barrett); and new theories for understanding change processes (Gomez & Ballard). The universal constant is change, and various ideas about sustaining change (Fredberg, Norrgren & Shani), mapping momentum changes during change efforts (Jansen & Hoffman) and exploring Lewins notions of the criticality of social space to facilitate change (Friedman). Volume 19 demonstrates that as academics, we advance the work in our field by both looking forward and looking back. Understanding the origins of our theories and beliefs can be as important as pioneering new ideas and methodologies. As you read Volume 19, we ask you to consider your own contributions to our field and to contact us to suggest topics for future volumes.